People's Land Use Guidelines for Incinerating Waste and Burning Agricultural Crops Affect Toxic Pollution - Noynalum, Thitaporn (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2023)
The purpose of this research article is to find answers to the land use practices of the people in waste burning and agricultural crops. with the participation of government agencies local government organizations and the public in order to comply with the management of air pollution The research methodology is qualitative research consisting of document research in-depth interview focus group in order to bring the answers to the preparation of local laws The research findings were that the legal authority of local government organizations in administration came from the law on formulation of plans and procedures for the decentralization of power to local government organizations, 1999, and the law on the establishment of local government organizations. for the preparation of local ordinances that give power and duty to government officials The answers have led to the preparation of a local ordinance on the management of waste burning and burning of agricultural crops that defines the authority of local government organizations and the participation of the people in order to achieve resource utilization. Smarter and Sustainable The research suggests the issuance of a local ordinance on the management of waste burning and agricultural burning of crops B.E. 2023 Has the authority to manage the community. together with government officials and the public